Simulation study of distribution cable insulation health assessment - Muhammad Aidil Azman (Nanyang Technological University, 2022)
A significant amount of research has been published in recent years on cable degradation and methodologies of Insulation Resistance Profile in XLPE cables. However, few have been published on simulating these processes. In this paper, summary results of simulations performed on cable insulation systems will be provided and compared to the results obtained by monitoring. We will study the effects of cable length, percentage of local defect, and defect position on the value of insulation resistance (IR) and insulation health status. We access the insulation health using IR and dielectric absorption ratio (DAR) when incorporating local defect into the system models.